The pedagogical bag: the reality of the concept and its uses in the field of teacher training - Boudiaf, Samira (Journal of Human Sciences, 2022)
The methods of educational assessment have been numerous and their fields of use varied, in addition to performance tests, which are included in the so-called traditional evaluation, other methods appeared that measure the performance and psychological aspects of the learner, including observation, performance tests, evaluation grids accompanied by the pedagogical bag which is the subject of this article which tries to identify the truth of this method, the stages of its preparation as well as its uses and functions in the field of teacher training.